The Effectiveness of Scrapbook on Learning Outcomes of 10th Grade Students Public Senior High School 6 Pontianak on Protista Subject - Putri, Elsa Putri; Yeni, Laili Fitri; Titin, Titin (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Protista are one of the the subject is quite broad and there are many Latin terms and objects, most of whichare micro organisms or living things that cannot be found and observed directly in everyday life, studentsare not enough to only have the ability to memorize but also need a complete understanding of the materialsuch as can classify and classify protista through morphological observations. So that students need a mediathat is interesting to them and easy to understand. The purpose of this research to see the effectiveness ofusing scrapbook media on student learning outcomes in class X protista material at SMA Negeri 6Pontianak. The form of the research is Quasi Experimental Design with the research design of Nonequivalent Control Group Design. The sample of this research is class X MIA 2 (control class) and X MIA3 (experimental class). Intact Group sampling technique. The instrument used is a multiple choice test with20 questions. The average score of the experimental class students' learning outcomes was 15.40 while thecontrol class's average score was 14.39. Based on the results of the Mann-Whitney U test, Z count . isobtained < Z table with a value of -2.74 < -1.96 so that it can be concluded that H0 is rejected and Ha isaccepted, where there are differences in the learning outcomes of students who are taught using scrapbookmedia and students who are taught using image media. Based on the results of the Effect Size learning usingscrapbook media, it got a value of 0.73 with the medium category meaning that the effectiveness of learningusing scrapbook media on protista material was classified as moderate in improving the learning outcomesof class X students of SMA Negeri 6 Pontianak by 26.73%.